The theory of polystylism as a tool for analysis of contemporary music in the postsoviet cultural space : some terminological aspects - Jaunslaviete, Baiba (Array, 2019)
The aim of this article is to discuss some essential concepts related to polystylism – a term first defined by Alfred Schnittke in 1971 and widely used within the post-Soviet cultural space. In the research conducted by various English-speaking musicologists, the term polystylism appears rarely and mostly in relation to Schnittke’s own music, whereas the related concepts of collage and borrowing are covered much more comprehensively. However, collage can be viewed as only a part of polystylism, because it includes only sharp stylistic juxtapositions and does not reflect other forms of stylistic interaction that could be described as diffuse, or symbiotic, polystylism. The theory of borrowing, for its part, covers a chronologically wide range of music (cantus firmus technique, quodlibet, paraphrase, etc.) but does not reflect the specifics of the 20th/21st-century music. The ability to cover these specifics is an advantage of polystylism and related terms, and therefore their broader integration into the international musicological lexicon should be encouraged.